Pengembangan trainer smart relay zelio sr3b261bd sebagai media pembelajaran pada mata pelajaran sistem pengendali elektronik - Desmira Desmira; Endi Permata; Mohammad Fatkhurrokhman; Irwanto Irwanto; Novi Noviyanti (Universitas Sarjanawiyata Tamansiswa, 2021)
This research aims to: (1) develop learning media trainer smart relay zelio SR3B261BD; (2) knowing the feasibility level of learning media trainer smart relay zelio SR3B261BD used in the subjects of electronic control system; and (3) knowing the level of effectiveness of learning media. The research method used is Reaearch and Development (R&D). The development model used is ADDIE with the following stages of research: analyze, design, development, implementation, evalution. The results of the study are: (1) the development of learning media trainer smart relay zelio SR3B261BD according to the design and equipped with a jobsheet and manual book, (2) the feasibility of learning media by media experts get an average score (X) of 3,31 â€œGood/decentâ€, the assessment of material experts received an average score (X) of 3,42 that is â€œvery good/well deservedâ€ and the user ratings are getting a score of 3,44 that is â€œvery good/very decentâ€, and (3) the effectiveness of learning media trainer smart relay zelio SR3B261BD get result score of 0,72 which is catagorized as â€œvery highâ€.Â